Optical and structural analysis of porous silicon coated with GZO films using rf magnetron sputtering - Prabakaran, R. (2007)
In the production of porous silicon (PS) to optoelectronic application one of the most significant constrains is the surface defects passivation. In the present work we investigate, gallium-doped zinc oxide (GZO) thin films deposited by rf magnetron sputtering at room temperature on PS obtained with different etching times. The X-ray diffraction (XRD), Fourier transform infrared (FTIR) and atomic force microscopy (AFM) analysis have been carried out to understand the effect of GZO films coating on PS. Further, the XRD analysis suggests the formation of a good crystalline quality of the GZO films on PS. From AFM investigation we observe that the surface roughness increases after GZO film coating. The photoluminescence (PL) measurements on PS and GZO films deposited PS shows three emission peaks at around 1.9 eV (red-band), 2.78 eV (blue-band) and 3.2 eV (UV-band). PL enhancement in the blue and ultraviolet (UV) region has been achieved after GZO films deposition, which might be originated from a contribution of the near-band-edge recombination from GZO.